Tiger can't sleep. - Fore, S. J. (New York : Viking, 2006)
A young boy is kept awake by the "talented" tiger in his closet that is busy dancing, eating and making music
K-3
Keywords: Bedtime - Fiction; Tigers - Fiction; Fear of the dark - Fiction; Alley, R. W. (Robert W.) illus